Strategies for resilience: results from a German pilot project to prevent far-right radicalisation within the police - Koehler, Daniel (Policing and society, 2024)
Preventing and countering potential far-right radicalisation within police forces is a major concern in many countries. Specific interventions such as anti-racism or intercultural competence training programmes for police officers are seen as key to build resilience against the lures of extremist ideologies and milieus. However, a dearth of empirical research investigating the factors that influence receptivity or rejection by the target group – police officers – impedes the design and implementation of effective interventions. This study presents findings from a formative evaluation accompanying a pilot project within the state police of the southern German state of Baden-Wuerttemberg called ‘Strategy Sponsorship for Democracy and Tolerance’. Drawing on three focus groups, five individual problem-centred interviews, and 603 feedback reports, the study finds that peer-to-peer approaches, voluntary participation, leadership support, freedom in topic selection and intervention planning, as well as budgetary independence positively impact the acceptance of interventions and motivation to engage. Age of participants, resource constraints and administrative challenges, as well as reservations about project aims and contents were found to increase the risk of rejection. Implications for optimising interventions for police forces are discussed.